2016
DOI: 10.7863/ultra.15.01068
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Risk of Malignancy Index for Discriminating Malignant Tumors in Women With Adnexal Masses

Abstract: The 4 RMI variants performed acceptably in a medium-resource setting where ultrasound examiners were physicians with varied experience. This finding indicates a good tradeoff between performance and feasibility, since ultrasound RMI protocols are of low complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
2
18
1
1
Order By: Relevance
“…Previous studies have demonstrated that, using subjective ultrasound evaluation, more than 50% of BOT were classified incorrectly as benign or unclassifiable and more than 60% were confused with other histopathological diagnoses. In addition, IOTA simple rules and non‐IOTA models had poorer performance for identifying BOT and Stage I OC than did the IOTA ADNEX model in our study. We found that the IOTA ADNEX model did not perform well in discriminating BOT and ovarian metastasis from Stage I OC.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies have demonstrated that, using subjective ultrasound evaluation, more than 50% of BOT were classified incorrectly as benign or unclassifiable and more than 60% were confused with other histopathological diagnoses. In addition, IOTA simple rules and non‐IOTA models had poorer performance for identifying BOT and Stage I OC than did the IOTA ADNEX model in our study. We found that the IOTA ADNEX model did not perform well in discriminating BOT and ovarian metastasis from Stage I OC.…”
Section: Discussioncontrasting
confidence: 59%
“…[9] , [14] The chances of ovarian malignancy increases in proportionate with the increasing age. [16] In the present study 76.36% were diagnosed with malignancy in postmenopausal group and 16.88% of the same group were with benign tumours. The Menopausal Status of our study gave a sensitivity of 72.7 % and specificity of 83.1% for diagnosing malignant cases.…”
Section: Discussionsupporting
confidence: 46%
“…Our study matched with B R Obiedat et al and Campos et al with a area under curve of 0.91 and 0.85 respectively. [16] , [18] In our study the ability of RMI to differentiate adnexal masses preoperatively as benign or malignant is statistically significant as shown by p value 0.0001 with odds ratio 427.6 (95% CI = 82.98 -2203 ). The combination of serum CA-125 level, USG morphology of pelvic mass and menopausal status have become the root cause for diagnosis of malignant pelvic masses.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A study from Brazil compared 4 different RMI models, and found them to have similar efficacy and success rates. The positive likelihood ratios of the 4 RMI variants were reported to range from 3.52 to 4.41 (13).…”
Section: Discussionmentioning
confidence: 99%